Hidrogen Sulfide Level and Respiratory Complaints of Officer in Garbage Management Super Depo Sutorejo Surabaya - Giannini Ludrya Putri (Universitas Airlangga, 2018)
Garbage is one source of air pollution. Hydrogen Sulfide (H2S) is a result of the decomposition of garbage that has an odor like rotten eggs, that will cause odor in the surrounding area. The respiratory system is the most sensitive organ for H2S in the air, so if exposed to this gas continuously can cause respiratory complaints in humans. The purpose of this study was to analyze the levels of H2S in the Super Depo Sutorejo and respiratory complaints on officers. This study used an observational study with cross-sectional approach. The samples were 21 people. Data were analyzed decriptively. H2S measurements held at two spot in the morning and afternoon. The results showed H2S levels between 0.6 Î¼g/m3 -1,4 Î¼g/m3. The result was still below the quality standard East Java Governor Regulation Number 10 of 2009 which is 42 Î¼g/m3 or 2 ppm. 16 people (76.2%) had experienced respiratory complaints. Perceived respiratory complaints included cough (57.1%), shortness of breath (23.8%) and itchy throat (52.4%). The conclusion of this study was H2S levels in Super Depo Sutorejo still below the quality standard established and the most respiratory complaints suffered by officer was cough.